Traditional Knowledge and Usage of Edible Plants among Temuan Community in Gunung Ledang Johor National Park, Malaysia - Sabran, Siti Fatimah (Journal of Sustainable Natural Resources, 2020)
Edible plants are important for their nutrient values as part of human diet and as food resources that are essential in times of food shortage. Due to the rapid declining usage of edible plants, loss of traditional knowledge and food security issues have caused the urgent need to document and safeguard the edibles knowledge especially among indigenous people. The objectives of this study were to document edible plant species used by Temuans in Gunung Ledang Johor National Park and to determine the relative value of the plants. The data was collected through a semi-structured interview and free listing technique that were applied to all 85 informants in the nearest village to the national park. Frequency Citation (FC), utilization of frequency (f), Cultural Importance Index (CI), and Cultural Food Significance Index (CFSI) were used to evaluate the relative importance of the different edible plants. A total of 43 edible plant species belonging to 22 families and 33 genera were recorded in the study.